Кісти яєчників. Аналіз структури патології у жінок репродуктивного віку - Шаповал, Ольга Сергіївна (My University, 2016)
Проблема конкретизації характеру кіст яєчників та тактика їх подальшого ведення займає одне з провідних місць в гінекологічній практиці. Частота об’ємних утворень яєчників у жінок репродуктивного віку в структурі гінекологічної патології складає 7,48 %. В структурі доброякісної патології яєчників частота функціональних кіст складає 77,82 %, ендометріоїдних та дермоїдних – 8,27 %, кістом яєчника – 4,89 %. The problem of treatment of patients with ovarian cysts is the one of main problems in the modern gynecological practice. The use of the results of the different modern methods of diagnostics can essentially shorten the time for setting the clinical diagnosis that is to choose the correct treating tactics in proper time. The aim of work was to analyze the structure of tumor-like formations of ovaries in women of reproductive age. Methods of research. There was carried out the retrospective analysis of 3555 medical histories of patients of reproductive age, who were hospitalized in gynecological department during 2009–2014 and underwent surgical and conservative treatment. The endoscopic optics, made by “Wing” (Russia) was used at laparoscopy. Laparoscopy and histological study of the samples of tissue were carried out according to the standard methods. The data were processed using the statistical program package STATISTICA (StatSoft statistica v.6.0).
Keywords: кісти яєчників; кістоми; репродуктивний вік; ультразвукова діагностика; онкомаркери; лапароскопія; гістологія; ovarian cyst; cystoma; reproductive age; ultrasound diagnostics; tumor markers; laparoscopy; histology